The Role of Pancreatic Enzyme Insufficiency in the Etiology of Functional Dyspepsia Resistant to Standard Treatment - Kemik, Fatih; Ceylan, Gozde; Aydin, Abdurrahman F.; Çavuş, Bilger; Ormeci, Asli; Imanov, Ziya; Senkal, Ibrahim V.; Nuriyev, Kenan; Istemihan, Zulal; Akyuz, Filiz; et al. (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Functional dyspepsia (FD) is diagnosed in the absence of an identifiable organic cause. Pancreatic enzyme insuf ficiency (PEI) remains an underrecognized condition in these patients. This study aimed to investigate the prevalence of PEI among FD patients unresponsive to standard therapy and to evaluate its clinical and biochemical characteristics. Materials and Methods: A total of 154 patients diagnosed with FD were followed, among which 66 patients who did not respond to at least 4 weeks of standard treatment, including acid-reducing therapies, prokinetics, and antidepressants, were evaluated. Additionally, 34 healthy volunteers were included as a control group. Organic pathologies were excluded in all 66 patients with FD resistant to stan dard treatment using endoscopy, endoscopic biopsy, and imaging methods. Fecal elastase-1 (FE-1) enzyme levels were measured to determine the prevalence of PEI in both groups. Results: Pancreatic enzyme insufficiency was detected in 5 (7.57%) of the 66 treatment-resistant FD patients, while none of the con trols had PEI. The prevalence of PEI was significantly higher in diabetic patients than in non-diabetic patients within the study group (P = .037). Patients with diarrhea, sticky stools, and frequent foul-smelling stools exhibited a higher prevalence of PEI (P = .022, P = .001, and P = .004, respectively). In the study group, PEI patients had lower serum calcium, phosphorus, and magnesium levels than the control group (P = .018, P = .011, and P = .001, respectively). Conclusion: Pancreatic enzyme insufficiency was identified in 7.57% of patients resistant to standard treatment. In patients resistant to standard therapy for at least 4 weeks, the presence of symptoms such as diarrhea, sticky stools, and foul-smelling stools, along with diabetes mellitus and low serum calcium, phosphorus, and magnesium levels, may warrant consideration of PEI as a potential underlying condition. Cite this article as: Kemik F, Ceylan G, Aydin AF, et al. The role of pancreatic enzyme insufficiency in the etiology of functional dyspepsia resistant to standard treatment. Turk J Gastroenterol. 2025;36(7):467-473.